SUBJECTIVE SOCIAL STATUS MODERATES BACK PAIN AND MENTAL HEALTH: A LONGITUDINAL ANALYSIS OF OLDER MEN. (20th December 2022) - Mu, Christina; Jester, Dylan; Cawthon, Peggy; Stone, Katie; Lane, Nancy; Lee, Soomi
Abstract: Objectives. This study tested the longitudinal relationship between back pain and mental health and examined the moderating role of subjective social status (SSS). Method. Community-dwelling older men from the MrOS Study provided four study visits of data collected between 2000-2016 (15, 975 observations nested within 5, 979 participants). Back pain frequency and severity were assessed at visits 1-4. General mental health was measured at each visit by the 12-item Short Form Survey Mental Component Score (SF-12 MCS; higher scores representing better mental health). National and community SSS were assessed at visits 1 and 3 with the MacArthur Scale. Growth curve models tested longitudinal within-person change associations after accounting for the repeated measures within each person. Age was used as the primary time variable. Results. At baseline, those with higher back pain-frequency/severity reported lower SF-12 MCS. After accounting for this between-person difference, there were bidirectional within-person associations between back pain frequency/severity and SF-12 MCS. On follow-up visits when back pain frequency/severity increased from baseline, participants reported lower SF-12 MCS (p<.001). On follow-up visits when SF-12 MCS decreased from baseline, participants also reported higher back pain frequency/severity (p<.001). Higher national and community SSS at baseline and having increases or consistently higher SSS over time attenuated the negative relationships between back pain frequency/severity and SF-12 MCS. Results were consistent after controlling for an extensive list of baseline health covariates and pain medications. Discussion. These findings highlight how self-perceived social status may buffer the relationship between greater back pain frequency/severity and lower mental health.